On an asymptotic formula for the niven numbers - Curtis N. Cooper; Robert E. Kennedy (International Journal of Mathematics and Mathematical Sciences)
A Niven number is a positive integer which is divisible by its digital sum. A discussion of the possibility of an asymptotic formula for N(x) is given. Here, N(x) denotes the nmber of Niven numbers less than x. A partial result will be presented. This result will be an asymptotic formula for Nk(x) which denotes the number of Niven numbers less than x with digital sum k.